The current state of the problem, clinical-pathogenetic approaches to the diagnosis and management tactics of fetal growth restriction - Puchkov, V. A.; Siusiuka, V. G.; Deinichenko, O. V.; Sergiyenko, M. Yu.; Boguslavska, N. Yu.; Babinchuk, O. V.; Пучков, Володимир Анатолійович; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна; Сергієнко, Марина Юріївна; Богуславська, Наталія Юріївна; Бабінчук, Олена Василівна (My University, 2024)
Fetal growth restriction is a common complication of pregnancy with a complex etiology and limited possibilities of diagnosis and treatment. The relevance of this difficult obstetric problem is determined by various published diagnostic criteria, relatively low detection rates, and limited options for prevention and treatment. Fetal growth restriction is defined as the inability of the fetus to reach its genetically determined growth potential, most often due to abnormal placentation. Forms of fetal growth restriction with early or late onset are distinguished based on the gestational age determined during prenatal ultrasound diagnosis. According to most recommendations, the 32nd week of pregnancy is set as the cut-off point for distinguishing between early and late onset fetal growth restriction. The definition underlying this classification is based on differences between these two phenotypes of fetal growth restriction in severity, natural history, Doppler findings, association with hypertensive complications, placental features, and management. It is important to distinguish two separate conditions: fetal growth restriction and small-for-gestational fetus, which differ in short-term and long-term perinatal outcomes. A fetus is defined as small for gestational age if the estimated weight or weight of the fetus at birth is below the 10th percentile. Fetal growth restriction is diagnosed if the estimated fetal weight is below the 3rd percentile or a combination of pathological blood flow in the umbilical arteries and/or uterine arteries in fetuses with an estimated weight below the 10th percentile. It can also occur in fetuses and newborns with a body weight above the 10th percentile. The need to distinguish between fetal growth restriction and small-for-gestational-age fetus is related to the fact that fetal growth restriction is the main cause of stillbirth, neonatal death, higher perinatal morbidity, as well as increased risk of diseases in adulthood. The article analyzes the approaches to differentiating fetal growth restriction from small growth retardation in terms of fetal gestation period and further increasing the accuracy of diagnosis, as well as the modern concept of pathogenesis, with an emphasis on oxidant stress as a key molecular mechanism of adverse outcomes. Appropriate interventions during pregnancy to reduce perinatal complications should include antenatal monitoring and drug therapy. Затримка росту плода належить до поширеного ускладнення вагітності зі складною етіологією та обмеженими можливостями діагностики та лікування. Актуальність цієї непростої акушерської проблеми зумовлена різними опублікованими діагностичними критеріями, відносно низькими показниками виявлення та обмеженими варіантами профілактики і лікування. Затримка росту плода визначається як нездатність плода досягти свого генетично зумовленого потенціалу росту, частіше за все внаслідок аномальної плацентації. На підставі гестаційного віку, визначеного під час пренатальної ультразвукової діагностики, виділяють форми затримки росту плода з раннім або пізнім початком. Згідно з більшістю рекомендацій, 32-й тиждень вагітності встановлено як граничну точку для розмежування раннього та пізнього початку затримки росту плода. Визначення, що лежить в основі цієї класифікації, ґрунтується на відмінностях між цими двома фенотипами затримки росту плода у тяжкості, природному перебігу захворювання, результатах допплерографії, зв’язку з гіпертензивними ускладненнями, плацентарними ознаками та лікуванням. Важливо виділяти два окремі стани: затримка росту плода та малий щодо терміну гестації плід, які відрізняються за короткостроковими та довгостроковими перинатальними наслідками. Малий щодо терміну гестації плід визначають, якщо розрахункова маса або маса плода при народженні нижче 10-го процентиля. Затримку росту плода діагностують, якщо розрахункова маса плода нижче 3-го процентиля або поєднання патологічного кровотоку в артеріях пуповини та/або маткових артеріях у плодів з розрахунковою масою нижче 10-го процентиля. Також може бути у плодів та новонароджених з масою тіла вище 10-го процентиля. Необхідність розрізняти затримку росту плода та малий щодо терміну гестації плід пов’язана з тим, що затримка росту плода є основною причиною мертвонародження, неонатальної смерті, більш високої перинатальної захворюваності, а також підвищеного ризику захворювань у дорослому віці. У статті проаналізовано підходи до диференціації затримки росту плода від малого щодо терміну гестації плода та подальшого підвищення точності діагностики, а також сучасну концепцію патогенезу, з акцентом на оксидантний стрес як ключового молекулярного механізму несприятливих наслідків. Відповідні заходи під час вагітності, які сприятимуть зменшенню перинатальних ускладнень, повинні включати антенатальний моніторинг та медикаментозну терапію.
Сучасний стан проблеми, клініко-патогенетичні підходи до діагностики і тактики ведення затримки росту плода
Keywords: fetal growth restriction; perinatal outcome; oxidant stress; antioxidants; затримка росту плода; перинатальний результат; оксидантний стрес; антиоксиданти